2014
DOI: 10.1111/tri.12379
|View full text |Cite
|
Sign up to set email alerts
|

The ins and outs of microRNAs as biomarkers in liver disease and transplantation

Abstract: Summary Ongoing research is being conducted in the field of transplantation to discover novel, noninvasive biomarkers for assessment of graft quality before transplantation and monitoring of graft injury after transplantation. MicroRNAs (miRNAs) are among the most promising in this field. MiRNAs are small noncoding RNAs that function as important regulators of gene expression in response to cellular stress and disease. An advantage that makes miRNAs attractive candidates for biomarker research is their fast re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 87 publications
1
24
0
Order By: Relevance
“…Because of their cell-type abundancy, extracellular miRNAs are increasingly being investigated as non-invasive biomarkers in serum for various liver diseases (7,15). Recently, in concordance with other human and animal studies (8,9,16), our team has demonstrated the specific release of hepatocyte-derived miRNAs (HDmiRs) in blood during liver injury, chronic hepatitis C infection and acute rejection after liver transplantation (LT) (17,18).…”
mentioning
confidence: 66%
“…Because of their cell-type abundancy, extracellular miRNAs are increasingly being investigated as non-invasive biomarkers in serum for various liver diseases (7,15). Recently, in concordance with other human and animal studies (8,9,16), our team has demonstrated the specific release of hepatocyte-derived miRNAs (HDmiRs) in blood during liver injury, chronic hepatitis C infection and acute rejection after liver transplantation (LT) (17,18).…”
mentioning
confidence: 66%
“…In the search for viable biomarkers, microRNAs (miRNAs) have gained interest due to their low complexity, stability, and organ specificity. Many studies have shown that miRNAs released in biofluids like serum, urine, and bile can be used as sensitive and accurate biomarkers . They are associated with a variety of pathologic conditions and control many cellular processes including tissue injury and repair .…”
mentioning
confidence: 99%
“…Many studies have shown that miRNAs released in biofluids like serum, urine, and bile can be used as sensitive and accurate biomarkers . They are associated with a variety of pathologic conditions and control many cellular processes including tissue injury and repair . Therefore, circulating miRNAs might be helpful contributors in the existing decision‐making models to either accept or decline a potential donor liver for transplantation in order to optimize graft and patient survival.…”
mentioning
confidence: 99%
“…They can down‐regulate certain processes by preventing translation of messenger RNA (mRNA) into functional proteins whereas others upregulate other cellular functions . Several studies have recently investigated the release of miRs in relation to cellular injury resulting from liver transplantation . It was shown that not only levels of released miRs differ between damaged and normal functioning hepatocytes and cholangiocytes but also that, during impaired excretory function and injury of hepatocytes, the liver shows polarized release of extracellular hepatocyte‐derived miRs (HDmiRs) and cholangiocyte‐derived miRs (CDmiRs) into both bile and serum, suggesting active rather than passive underlying release mechanisms …”
Section: Introductionmentioning
confidence: 99%
“…9 Several studies have recently investigated the release of miRs in relation to cellular injury resulting from liver transplantation. [10][11][12][13] It was shown that not only levels of released miRs differ between damaged and normal functioning hepatocytes and cholangiocytes but also that, during impaired excretory function and injury of hepatocytes, the liver shows polarized release of extracellular hepatocyte-derived miRs (HDmiRs) and cholangiocyte-derived miRs (CDmiRs) into both bile and serum, suggesting active rather than passive underlying release mechanisms. 14 The aim of the current study was to assess whether miRs in the perfusate and bile of normothermically perfused liver grafts correlate with, and are predictive of, hepatocellular and cholangiocellular injury and liver function as measured by currently available indicators and classic markers.…”
Section: Introductionmentioning
confidence: 99%